Sharia Swimming Pool: A Practice and the Factors that Affect Consumers - Alam, Azhar; Sukmana, Raditya; Sholikah, Nikmatus; Jim, Mahafizur Rahman (UIN Sunan Gunung Djati Bandung, 2024)
The swimming pool is a part of tourism, entertainment, and sports activities. The development of halal tourism demands swimming pool facilities that can better meet Sharia principles that benefit Muslim consumers. This study aims to reveal Sharia swimming pool management practices and explore why its customers choose Sharia swimming pools over conventional swimming pools. This research was conducted to reveal the halal lifestyle that has penetrated halal tourism, including swimming pools based on Sharia principles. This study uses a phenomenological approach to reveal the phenomenon of swimming pool practices and factors that affect its customers. This study interviewed 15 people with characteristics of high-intensity Sharia swimming pool use. It revealed that Islamic pool management practices include rules for members to enter, swimwear, facilities, and services provided. This study explores the factors influencing Islamic pool consumers by grouping them internally and externally. Internal factors impacting Sharia swimming pool users include comfort, halal lifestyle, and health. At the same time, the support of facilities, encouragement from others, and unpleasant experiences in public or traditional swimming pools are part of external factors. This study is expected to become a reference for Sharia swimming pool management practices and evidence of the findings of factors that encourage consumers to choose Sharia swimming pools.